A method for identifying common and unique issues in body in white dynamic stiffness based on modal contribution analysis - Feitan Peng; Luteng Chen; Junyi Ye; Fuwu Yan (Scientific Reports)
Abstract This study examines the problem of inadequate dynamic stiffness at the connection points of car bodies. A method based on modal contribution analysis to assess whether the cause of inadequate dynamic stiffness is a common or unique problem is proposed. Taking the front engine compartment attachment point of a body-in-white as a case study, this research identifies common issues arising from overall modes within the low-frequency range (54/58/74 Hz). To address the problem of frequency mismatch due to different modal truncation frequencies, the left front mounting point of the upper control arm is taken as an example, where the dynamic stiffness at 120 Hz is 8324 N/mm. Through modal contribution analysis, it was identified that the 46 th order engine compartment breathing mode contributed the most, confirming this as a common issue. Common issues can be optimized through frequency avoidance, while unique issues can be optimized using Operational Deflection Shape (ODS) analysis. Early identification of whether an issue is common or unique can significantly enhance the efficiency of NVH (Noise, Vibration, and Harshness) optimization for the vehicle body.